2016
DOI: 10.1124/mol.116.106070
|View full text |Cite
|
Sign up to set email alerts
|

Non-cell-autonomous Effects of Autophagy Inhibition in Tumor Cells Promote Growth of Drug-resistant Cells

Abstract: Autophagy, the mechanism by which cells deliver material to the lysosome, has been associated with resistance to anticancer drugs, leading autophagy inhibition to be widely studied as a potential chemosensitization strategy for cancer cells. This strategy is based on the idea that inhibition of autophagy will increase drug sensitivity and kill more cancer cells. Here we report an unintended negative effect of this strategy. When modeling the effect of drug resistance in a heterogeneous cancer cell population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…What are the cellular and cancer contexts in which autophagy inhibition will be therapeutically beneficial [22,394,395,396]? Are there indirect or direct caveats to autophagy inhibition in certain cancer contexts, and how can we minimize them [395,397,398]? Are there clinical and/or molecular tumor features that will allow us to better stratify patients that may benefit from autophagy inhibition in treatment [399,400,401,402]?…”
Section: Discussionmentioning
confidence: 99%
“…What are the cellular and cancer contexts in which autophagy inhibition will be therapeutically beneficial [22,394,395,396]? Are there indirect or direct caveats to autophagy inhibition in certain cancer contexts, and how can we minimize them [395,397,398]? Are there clinical and/or molecular tumor features that will allow us to better stratify patients that may benefit from autophagy inhibition in treatment [399,400,401,402]?…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy was firstly linked to tumorigenesis when monoallelic deletion of Beclin1, a modulatory gene on autophagy, was found in breast and ovarian cancers [26]. In contrast, studies have also demonstrated that autophagy inhibition enhanced cytotoxic effects of chemotherapy but promoted proliferation in certain cellular context [27, 28], suggesting that autophagy may play a role in cancer survival under stress. Autophagy provides not only the nutrients and energy but also the cellular restructuring in response to metabolic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers using clinical samples showed that autophagy was inhibited in patients with high expression of G6PD and ADRB2, or low expression of PTEN and FAT4, contributing to the resistance to lapatinib, 57 sorafenib, 58 trastuzumab 59 and ceritinib, 60 through degradation of HIF1α or promoting epithelial–mesenchymal transition. Additionally, experimental studies also observed that inhibiting autophagy can promote tumor resistance to diphtheria toxin-EGF 61 and sorafenib, 62 by activating caspase and PGE 2 signaling pathways or miR-21 mediated Akt/PTEN signaling pathway. And inhibiting the Akt pathway can activate autophagy to exert autophagy-dependent cell death, thus reversing the acquired resistance.…”
Section: The Important Role Of Autophagy In Tumor Resistancementioning
confidence: 99%